In Situ Deposition of Gold Nanoparticles and L-Cysteine on Screen-Printed Carbon Electrode for Rapid Electrochemical Determination of As(III) in Water and Tea - Wenjing Wang; Zhijian Yi; Qiongxin Liang; Junjie Zhen; Rui Wang; Mei Li; Lingwen Zeng; Yongfang Li (Biosensors, 2023)
In this study, a screen-printed carbon electrode (SPCE) based on in situ deposition modification was developed for the sensitive, rapid, easy and convenient determination of As(III) in water and tea by linear sweep anodic stripping voltammetry (LSASV). The screen-printed carbon electrodes were placed in a solution consisting of As(III) solution, chlorauric acid and L-cysteine. Under certain electrical potential, the chloroauric acid was reduced to gold nanoparticles (AuNPs) on the SPCE. L-cysteine was self-assembled onto AuNPs and promoted the enrichment of As(III), thus enhancing the determination specificity and sensitivity of As(III). The method achieved a limit of determination (LOD) of 0.91 ppb (µg L−1), a linear range of 1~200 µg L−1, an inter-assay coefficient of variation of 5.3% and good specificity. The developed method was successfully applied to the determination of As(III) in tap water and tea samples, with a recovery rate of 93.8%~105.4%, and further validated by inductively coupled plasma mass spectrometry (ICP-MS). The developed method is rapid, convenient and accurate, holding great promise in the on-site determination of As(III) in tap water and tea leaves, and it can be extended to the detection of other samples.